Social Management in Organizations and its Contribution to Human Groups A Perspective from Comparative Case Studies (2018)
Taking the social management process as a problem, this book deals with organizations as a fundamental part of the life of human beings. The research focuses on case studies in order to characterize social management processes in Colombian organizations, identify categories in which transformations have taken place, propose broad lines for strengthening their responsibility to human beings, their surroundings and environment, and detect development and management trends as new references in business administration. Constant realization and integration of theory and practice, through a comparative historical-hermeneutic methodology, represents a valuable search in the understanding of collective human experiences, within specific historical spheres, both spatially and temporally. Exploring the dynamics and dialectics of social management, expressed at different levels and in various dimensions, in several organizations belonging to four sensitive economic sectors of a country enables the reader to extrapolate findings as well as to comprehend and analyze approaches to possibilities and limitations of social development.